Potensi Ekstrak Etanol Daun Kelor (Moringa Oleifera) Terhadap Kualitas Spermatozoa dan Hormon Testosteron Tikus Putih Jantan yang Diinduksi Meloxicam - Ayustina, Putu Mila; Rai Suarni, Ni Made; Ermayanti, Ni Gusti Ayu Manik (Metamorfosa: Journal of Biological Sciences; Vol 9 No 2 (2022), 2022)
Meloxicam is a Non-Steroidal Anti-Inflammatory Drug (NSAID) given to humans and animals to treat inflammation that is most widely prescribed. The use of meloxicam that is not in accordance with the dose and in the long term will cause a toxic effect of meloxicam. Meloxicam can trigger oxidative stress and has a mechanism of inhibition of prostaglandin synthesis that can affect hormonal regulation and male reproduction. The purpose of this study was to analyze potential of ( Moringa oleifera ) leaf ethanol extract on sperm quality and testosterone hormone of male white rats ( Rattus norvegicus ) induced meloxicam. The design used was a (CRD) Completely Randomized Design consisting of three treatments and two controls with six replications. The treatment was given for 35 days. Meloxicam was given at a dose of 8,4 mg/kg body weight and moringa extract at a dose of 200 mg/kg body weight/day (P1), 400 mg/kg body weight/day (P2), and 600 mg/kg body weight/day (P3). The results showed that moringa extract dose of 400 mg/kgBW and 600 mg/kgBW has the potential to increase reproductive organ weight, motility, spermatozoa viability, spermatozoa count, and increase testosterone levels significantly (P<0,05).